2021
DOI: 10.1002/joc.7267
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between NDVI, river discharge and climate in the Okavango River Basin region

Abstract: The Okavango River Basin (ORB) is a highly sensitive and biodiverse region in southern Africa whose climate, vegetation and river discharge characteristics are not well understood. This study investigated relationships between rainfall, temperature, Normalized Difference Vegetation Index (NDVI) and river discharge over the region as well as their trends and interannual variability. It is found that spatial patterns of NDVI are closely related to those of rainfall, but less so with temperature at monthly and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 90 publications
(142 reference statements)
5
20
0
Order By: Relevance
“…The SatVITS-Flood model scheme effectively detects and correlates floods with changes derived from satellite vegetation indices. These results, aligned with previous research, demonstrate the potential of time series analysis of satellite vegetation indices in the flood monitoring and prediction (Fu & Burgher, 2015;Grodek et al, 2020;Manning et al, 2020;Moses et al, 2021). The use of NDVI as a measure of vegetation sensitivity to changes in water supply, and the selection of pixels with a high NDVI annual standard deviation closest to the riverbank, provided an effective way to identify areas likely to be affected by floods, consistent with previous studies that have used NDVI for similar related purposes Helman and Mussery, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The SatVITS-Flood model scheme effectively detects and correlates floods with changes derived from satellite vegetation indices. These results, aligned with previous research, demonstrate the potential of time series analysis of satellite vegetation indices in the flood monitoring and prediction (Fu & Burgher, 2015;Grodek et al, 2020;Manning et al, 2020;Moses et al, 2021). The use of NDVI as a measure of vegetation sensitivity to changes in water supply, and the selection of pixels with a high NDVI annual standard deviation closest to the riverbank, provided an effective way to identify areas likely to be affected by floods, consistent with previous studies that have used NDVI for similar related purposes Helman and Mussery, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…The general idea that floods in hyperarid regions can be detected using satellite-derived spectralbased indices leans on two main observations: (1) floods have an indirect impact on the riverbank vegetation by recharging the shallow aquifers and improving water quality (Dahan et al, 2008;Grodek et al, 2020) and (2) the changes in the vegetation cover, vigor, and growth, of both ephemeral (mainly annual herbaceous) and perennial (mainly evergreen, woody) plant species, can be detected via spectral-based vegetation indices from satellites (Grodek et al, 2020;Moses et al, 2021;Normandin et al, 2022). Figure 1 illustrates an example of the indirect effect of a flood on the riverbank vegetation in a hyperarid region and how such an effect is detected in a time series of a vegetation index (VI).…”
Section: The Logic Underlying the Use Of VI Time Series For Flood Det...mentioning
confidence: 89%
See 1 more Smart Citation
“…The results of this study underscored the importance of lag times in explaining patterns of productivity in semi‐arid floodplains. The lagged responses have been noted for other semi‐arid and arid‐zone floodplain wetlands, including the Tarim River, northwest China (Liao et al, 2020) and the Okavango River Basin in Africa (Moses et al, 2021). While rainfall in the season of measurement was an important predictor of productivity for E. largiflorens and E. camaldulensis , rainfall in the previous season was more important for D. florulenta productivity and also improved the prediction of productivity for E. largiflorens and E. camaldulensis .…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have reported that temporal variation of EVI is closely associated with rainfall (Budde et al, 2004;Doi, 2001;Richard and Poccard, 1998;Wang et al, 2003;Kumari et al, 2021). Although, there is a time lag of one or two months between EVI and rainfall (Moses et al, 2021;Kumari et al, 2021).…”
Section: Annual Variation Of Evimentioning
confidence: 99%